2014
DOI: 10.1371/journal.pone.0090235
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intracanal Irrigant MTAD Combined with Nisin at Sub-Minimum Inhibitory Concentration Levels on Enterococcus faecalis Growth and the Expression of Pathogenic Genes

Abstract: Exposure to antibiotics is considered to be the major driver in the selection of antibiotic-resistant bacteria and may induce diverse biological responses in bacteria. MTAD is a common intracanal irrigant, but its bactericidal activity remains to be improved. Previous studies have indicated that the antimicrobial peptide nisin can significantly improve the bactericidal activity of MTAD against Enterococcus faecalis. However, the effects of MTAD and its modification at sub-minimum inhibitory concentration (sub-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 25 publications
(43 reference statements)
0
10
0
1
Order By: Relevance
“…In our study, Nisin was incorporated at two different concentrations 1% and 5% in the fth generation BA. The concentration of Nisin was chosen in accordance to its minimum inhibitory concentration [23]. The results of our study showed that the growth of S. mutans was signi cantly higher in group I.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, Nisin was incorporated at two different concentrations 1% and 5% in the fth generation BA. The concentration of Nisin was chosen in accordance to its minimum inhibitory concentration [23]. The results of our study showed that the growth of S. mutans was signi cantly higher in group I.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons some authors proposed the association of the antimicrobial peptide nisin in the composition of Biopure MTAD ® . They found a significantly improvement on the bactericidal activity of Biopure MTAD ® against E. faecalis [23]. Currently, the use of Biopure MTAD ® as intracanal irrigant is more restrict to final irrigation, after the use of NaOCl as main irrigant [24].…”
Section: Contact Anglementioning
confidence: 99%
“…152 Importantly, E. faecalis does not seem to develop resistance toward nisin. 153 Another AMP with long-confirmed antimicrobial activity against oral pathogens is human b defensin-3 (HBD-3; [154][155][156] antimicrobial activity includes S. aureus, E. coli, Fusobacterium nucleatum, Prevotella melaninogenica, Peptostreptococcus anaerobius, S. mutans, Actinomyces naeslundii, E. faecalis, and C. albicans species, for example). 157 A smaller variant of HBD-3 (15 amino acids compared to 45; HBD3-C15 158,159 ) is able to reduce fungal growth in an ex vivo model of C. albicans-infected root dentin with similar effects as chlorhexidine.…”
Section: Dental Restorative Materials Modification With Ampsmentioning
confidence: 99%